Zinc (Zn) Removal from Textile Wastewater by Saw Dust Fixed Bed Column (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
The textile industry has been recognized as one of the industries that produces high discharged rate of wastewater with high volume and composition of contaminants to the environment. Zinc (Zn) is one of the contaminant that commonly found in textile wastewater. An investigation on the capability of saw dust to remove Zn in the textile wastewater was done. The abundance of saw dust produced from the saw mill will bring adverse effects on the environment. In this study, an investigation of Zn removal was carried out by using saw dust fixed bed column. The effect of types of sawdust, adsorbent dosage and adsorbent particle size to the Zn removal was studied. The results showed that the carbonized sawdust with 15g of adsorbent dosage and 150?m of adsorbent particle size gives the highest percentage of Zn removal with lowest time taken. This study indicates that sawdust has the potential to be employed as an adsorbent for Zn removal in textile wastewater.
Keywords: zinc; wastewater; fixed bed column